Encyclopedia of behavioral neuroscience - Koob, George F.; Le Moal, Michel; Thompson, Richard F. (Academic Press, 2010)
This work covers important research in all areas of behavioral neuroscience. Topics range from neuroethology and learning and memory, to behavioral disorders and psychiatric diseases, including addictions, anxiety, depression, schizophrenia, and autism.